Incidence of canine hip dysplasia - a prospective study of one year - Seesma Subramaniyan; P. T. Dinesh; S.Sooryadas; N.S. Jinesh Kumar; V. Remya; Hamza Palekodan (Journal of Veterinary and Animal Sciences, 2023)
A study was conducted to assess the prevalence of canine hip dysplasia (CHD) among dog population during a period of one year from January 2021 to December 2021. Canine hip dysplasia was confirmed by clinical orthopedic and radiographic examinations. Of the 231 dogs presented with lameness suspected to be originating from hip joint, 140 animals had dysplastic hips. The incidence was more in large breeds of dogs in an age group of 6 months to 12 months. Thirty five percent of the animals showed unilateral affection while in the remaining 65 percent it was bilateral. Females were more affected with this condition as per the findings of this study. Other than hip dysplasia, traumatic hip dislocation and osteoarthritis contributed to lameness originating from hip joints.